Detection and effects of methamphetamine on the lifecycle of sarcophagidae in Malaysia - Lian, Yong Zi (2025)
Forensic investigations often face challenges when determining the time and cause of death, especially in cases where remains are found in advanced decomposition. Forensic entomology, the study of insects that colonize decomposing remains, has become a crucial tool in forensic investigations, providing valuable insights into the post-mortem interval (PMI) and the cause of death. A more specialized field, forensic entomotoxicology, focuses on using insects to detect drugs and other chemical substances in decomposing tissues. Insects, particularly larvae, play a significant role in PMI estimation as they accumulate substances from decomposing bodies, offering a more sensitive method for detecting toxins with fewer interferences from decomposition by-products. The rising prevalence of methamphetamine (MA) abuse has led to numerous overdose deaths, where bodies are typically discovered after several days of decomposition. This delay complicates forensic investigations. To address this, forensic entomotoxicological analysis using insects is increasingly being used to detect the presence of drugs such as MA in decomposing tissues. In this study, pig liver mince was used to simulate the decomposition process and attract necrophagous insects, particularly Sarcophagidae. The liver was minced with two concentrations of MA (5 ng/mg and 10 ng/mg) to examine its impact on the lifecycle and morphology of Sarcophagidae. Samples were collected at various developmental stages for GC-FID analysis to detect MA presence. The results demonstrated that MA exposure delayed the lifecycle of Sarcophagidae, with insects exposed to 10 ng/mg MA taking 26 days to complete their lifecycle compared to 25 days for the 5 ng/mg MA-treated and control groups. Additionally, MA exposure resulted in a dose-dependent increase in the size and weight of larvae and pupae. However, adult flies from the MA-treated groups were slightly lighter compared to the control group. Notably, MA was detected in 3rd instar larvae at both concentrations and in adult flies at higher concentration, suggesting that the 3rd instar larvae are the most suitable stage for toxicological analysis